HEART RATE REPRODUCIBILITY ASSESSED BY SURROGATE DATA ANALYSIS - Goswami, Nandu; Rössler, Andreas; Lackner, Helmut Karl; Batzel, Jerry; Hinghofer-Szalkay, Helmut (Annales Kinesiologiae, 2015)
Purpose: Combinations of head up tilt (HUT) and lower body negative pressure (LBNP) have been used to study syncope. Since HUT invokes initial, partly transient cardiovascular responses, in this work we employed the HUT phase (5 min in all subjects) to arrive at a state of orthostatic loading to be used as a reference load for subsequent added LBNP phases. We investigated the pattern of cardiovascular responses during the LBNP phase across four runs for test subjects using surrogate data analysis. Methods: Ten healthy young males were subjected to HUT + LBNP to achieve a pre-syncopal end-point in four tests each separated by ≥2 weeks. Beat to beat continuous hemodynamic variables were measured and analyzed. Results: Expected heart rate and stroke volume responses changes during the LBNP phase were observed. Heart rate was the only variable that showed reproducibility between subjects across four runs. Conclusion: During LBNP phase of the combined HUT+ LBNP protocol, heart rate was the only reproducible variable, thus confirming its central role during added LBNP in upright tilted men. Surrogate data analysis is useful tool to differentiate physiological responses from chance events in repeated runs.